...the H-W equilibrium is given by: f(

**AA**) = p^2 f(**Aa**) =**2p**(1-p) f(**aa**) = (1-p)^2 http://en.wikipedia.org/wiki/Hardy%E2%80%...2 Answers · Social Science · 17/07/2011

It may be a file with the wrong font, but I think it is more likely that you have a file with the wrong extension (example: trying to read an executable file as text)

3 Answers · Society & Culture · 12/09/2010

... equilibrium= (p2) + (2pq) + (q2) = 1 f( AA )= p² f( Aa )= 2pq f( aa )= q² ------------------------- q²=0.3 q= 0.54 (p2) + ( 2p *0.54) + 0.3 = 1 p² + 1.09p= 0.7 p*(p + 1.09) =0.7 p=0.7 or p + 1.09...

1 Answers · Science & Mathematics · 09/04/2012

...outperform all the others. If p is the probability that any specific

**AA**bond outperforms the others, then**2p**is the probability that any specific AAA bond outperforms the...1 Answers · Science & Mathematics · 15/07/2013

...3e j 2n,B av c 2s,B au 14 2r,B bj 3 2q,B bj o

**2p**,B**aa**m 2o,B a5 13**2p**,B ak 6**2p**,B 9p u**2p**,B 9k 5 2n...1 Answers · Games & Recreation · 20/09/2011

...recessive, q'^2(

**aa**) = (0.67)^2 = 0.4489 and the frequency of heterozygotes,**2p**'q'(**Aa**) = 2 x 0.33 x 0.67 = 0.44222 Answers · Science & Mathematics · 05/06/2011

...1-p) = 0.48 you have new equation:

**2p**-**2p**^2 = 0.48 -**2p**^2 +**2p**- 0.48 = 0 And using the ABC formula... q = 1 - 0.6 = 0.4 Expected frequency of**AA**, p^2(**AA**) = 0.6^2 = 0.36 Expected frequency...2 Answers · Science & Mathematics · 31/05/2010

..., so here it is without Lagrange: P(p, q) = 2pq +

**2p**(1-p-q) + 2q(1-p-q) = 2pq +**2p**-**2p**^2 -2pq + 2q - 2q^2 -2pq =**2p**-**2p**^2+ 2q - 2q^2...1 Answers · Science & Mathematics · 06/06/2011

...antibonding σ2s* orbital, 4 more antibonding electrons in π 2p *). Bond order: (8 – 6)/2 = 1. Bond ...increase with decreasing in bond order: O₂ : 1.21 Å O₂⁻ : 1.33 Å O₂²⁻ : 1.49 Å ...

2 Answers · Science & Mathematics · 03/12/2009

...

**Aa**) = 2pq f(**aa**) = q^2 then: 0.91 = f(**AA**) + f(**Aa**) = p^2 + 2pq" But then since this is a... q=1-p So, 0.91 = p^2 + 2pq 0.91 = p^2 +**2p**(1-p) Solve for p p = 0.7 (70%) Confirm...3 Answers · Education & Reference · 19/03/2008